Electoral control when policies are for sale - Etienne Farvaque; Gaël Lagadec (Center for Economic Studies and ifo Institute (CESifo), 2009)
This article analyses the dynamics of electoral promises, building on an electoral competition model with endogenous policies. It extends the Grossman-Helpman (1994) model [Grossman G., Helpman E. [1994], Protection for sale, American Economic Review, 84, 4, 833-850] to include sanctions from the electorate and lobbies when the incumbent does not satisfy the expected performance she promised to deliver. This framework allows to deal with the intertemporal dimension needed to understand the prevalent cycle of promises, disappointment, new promises, new disappointment.
Keywords: D72; P16; 330; Lobbies; promises; elections; electoral competition; lies; Interessenpolitik; Wahlkampf; Wahl; Wettbewerb; Wahlverhalten; Theorie